2013
DOI: 10.1007/s00203-013-0935-1
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular expression of glucose inhibition-resistant Cellulomonas flavigena PN-120 β-glucosidase by a diploid strain of Saccharomyces cerevisiae

Abstract: The catalytic fraction of the Cellulomonas flavigena PN-120 oligomeric β-glucosidase (BGLA) was expressed both intra- and extracellularly in a recombinant diploid of Saccharomyces cerevisiae, under limited nutrient conditions. The recombinant enzyme (BGLA¹⁵) expressed in the supernatant of a rich medium showed 582 IU/L and 99.4 IU/g dry cell, with p-nitrophenyl-β-D-glucopyranoside as substrate. BGLA¹⁵ displayed activity against cello-oligosaccharides with 2-5 glucose monomers, demonstrating that the protein is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The adjusted-R 2 value for both ethanol and SCE represent the significance of the model. However, in saccharification, the accumulation of glucose to a certain extent causes the feedback inhibition of the cellulolytic enzyme, and shuts down the saccharification process [31,32]. Results from ANOVA demonstrate that all the four factors were found significant, based on their P values <0.05, for ethanol production.…”
Section: Anova Of Models Developed For Ethanol Production and Substramentioning
confidence: 95%
“…The adjusted-R 2 value for both ethanol and SCE represent the significance of the model. However, in saccharification, the accumulation of glucose to a certain extent causes the feedback inhibition of the cellulolytic enzyme, and shuts down the saccharification process [31,32]. Results from ANOVA demonstrate that all the four factors were found significant, based on their P values <0.05, for ethanol production.…”
Section: Anova Of Models Developed For Ethanol Production and Substramentioning
confidence: 95%
“…Chen et al [12] reported expression of a secretory β glucosidase from Trichoderma reesei in P. pastoris that the maximum recombinant β glucosidase activity achieved 60 U/mL. Mendoza Aguayo with coworkers [13] revealed extra cellular expression of β glucosidase of Cellulomonas fla vigena PN 120 in the supernatant of a rich medium showing 582 U/L. On the other hand, there are a few reports on expression and extracellular secretion of β glucosidase from the thermophilic bacteria in E. coli [9][10][11][12][13].…”
mentioning
confidence: 97%
“…Mendoza Aguayo with coworkers [13] revealed extra cellular expression of β glucosidase of Cellulomonas fla vigena PN 120 in the supernatant of a rich medium showing 582 U/L. On the other hand, there are a few reports on expression and extracellular secretion of β glucosidase from the thermophilic bacteria in E. coli [9][10][11][12][13]. The advantages of thermostable enzymes in industrial processes include reduced risk of contamina tion, increased substrate solubility, higher stable of enzymes against denaturing agents and proteolytic enzymes, and reduced cost of external cooling [14].…”
mentioning
confidence: 99%